Efficacy and safety of gastric peroral endoscopic myotomy (G-POEM) for refractory gastroparesis: 3-year follow up results - Chung, Chen-Shuan; Huang, Tien-Yu; Lin, Cheng-Lu; Chiang, Chen-Han; Chen, Kuan-Chih; Wu, Jiann-Ming; Chen, Kuo-Hsin; Lee, Tzong-Hsi; Lin, Cheng-Kuan; Wang, Hisu-Po (Journal of the Formosan Medical Association, 2022)
Gastroparesis is a common but easily overlooked disease. Gastric peroral endoscopic myotomy (G-POEM) is one of the third-space endoscopy techniques to treat gastroparesis. In this study, we aimed to evaluate the efficacy and safety of G-POEM for patients with refractory gastroparesis. Between December 2017 and 2020, we consecutively enrolled patients with gastroparesis who failed after the administration of several kinds of medication and repeated admission for nutritional support. All patients underwent gastric emptying scintigraphy and answered a questionnaire on Gastroparesis Cardinal Symptom Index (GCSI). Demographic data, endoscopic procedure, and post procedural outcome were analyzed. A total of 11 (9 women and 2 men) patients with refractory gastroparesis (nine with diabetes mellitus, one systemic lupus erythematosus, and one idiopathic) were enrolled. The mean (±standard deviation (SD)) procedure time was 61.82 (±18.99) min with technical and clinical success rates of 100% and 81.82%, respectively. A statistically significant improvement was observed in the clinical severity (mean GCSI score 36.00 vs. 14.73, p < 0.0001) and gastric emptying time (mean T1/2 341.92 vs. 65.92 min, p = 0.016) after G-POEM. Hospital stay was 7.18 (±4.49) days without mortality. Complications included 4 (36.36%) patients with self-limited postprocedural abdominal pain and 3 (27.27%) patients with intra-procedural pneumoperitoneum. During the mean follow-up period of 554.36 days, one (9.09%) patient had relapsed clinical symptoms after 6 months. G-POEM is an efficient and safe pylorus-directed endoscopic therapy for refractory gastroparesis with promising results.